The Overall Number of Actinic Keratosis Lesions Is Not Predictable by the Number of Visible Lesions: Consequences for Field-Directed Therapies - Eggert Stockfleth, MD PhD; Nathalie Bégeault, MSc; Alain Delarue, MD (Elsevier, 2022)
ABSTRACT: Actinic keratoses are keratotic lesions occurring on skin areas extensively damaged by sunlight. Using data from a previously published Phase III randomized, controlled clinical trial in patients with at least 5 actinic keratoses, we explored the potential link between the number of visible actinic keratosis lesions before any treatment and the total number of lesions of the field cancerization as revealed by 5-fluorouracil cream. Our analysis suggests that the baseline number of visible actinic keratoses is a poor indicator of the real number of lesions in the field of cancerization, reinforcing the need to explain the field cancerization concept to patients. (Curr Ther Res Clin Exp. 2022; 82:XXX-XXX) © 2022 Elsevier HS Journals, Inc.